THE IMPROVEMENT OF STUDENTS’ LEARNING OUTCOMES ON THE BASIC RHYTMIC MOTION MATERIAL USING THE JIGSAW METHOD OF COOPERATIVE LEARNING IN GRADE V OF MIN 16 WEST ACEH - Riki Irawan; Badrussalim Badrussalim (FKIP Universitas Al Washliyah Medan, 2021)
This study aims to determine the improvement of students’ learning outcomes on the basic rhythmic motion material using the jigsaw method of cooperative learning in Grade V of MIN 16 West Aceh. Each cycle had 4 stages. The research subjects were students of Grade V of MIN 16 West Aceh with a total of 22 students. In each cycle, the researcher provided a rhythmic gymnastics material with the jigsaw method of cooperative learning. The instrument used to assess the students was a test sheet of knowledge, performance and students’ attitudes which was filled out by the teacher. While the instruments used to assess the teachers were observation sheets of teachers’ abilities and students’ attitudes filled out by collaborators and student response questionnaires filled out by students after the learning was completed. The results showed that there was an increase in students’ learning outcomes who finally reached the KKM specified, namely 75, in which there was 90.9% with a total of 20 students and the percentage of those who had not been able to reach the KKM of 75 was 9.1% with a total of 2 students.